Tropaeolum Majus Leaves Extract as an Antifungal, Antiaflatoxigenic and Antiaflatoxin Agent - Mohammad J. Al-Jassani (Journal of Global Pharma Technology, 2018)
Tropaeolum majus‎is widely cultivated both as an ornamental and as a medicinal plant. All parts of the plant are edible and highly nutritive and it was evaluated for its antifungal, anti-oxygenic and anti-aflatoxin activity. T. majus leaves were collected and let to dry in a shady place then grinded. Total of 100g of dry plant was extracted successively with 250 ml of Absolute ethanol. The plant extracts’ anti-fungal activity were tested against aflatoxigenic Aspergillus spp. isolates by disc diffusion method and the MIC, MFC was determined using microdilution method. The microplate fluorescence imaging procedure was used for antiaflatoxin activity test. The ethanoilic extract of T. majus showed high antifungal activity against most selected aflatoxigenic Aspergillus isolates at 100mg/ml of MIC and MFC. The ethanoilic extract of T. majus showed high influence on the inhibition and depression of AFs production genes at MIC of 50mg/ml and MDC at 25mg/ml. The concurrent addition of the ethanoilic extract of T. majus (2 to 0.25mg/ml) to the RBC suspension cased a significant reduction in AFB1-induced hemolysis in a concentration-dependent effect manner. The results showed that 1.5mg/ml of T. majus ethanoilic extract was the best concentration that prevented aflatoxin-induced hemolysis with 100% AFB1 elimination. As a first report, T. majus leaves extract is highly recommended as an additive to the food and feedstuffs as a nutritive, antifungal and antitoxin agent.Keywords: Tropaeolum majus, Antifungal, Antiaflatoxigenic, Antiaflatoxin.